Tricin selectively combats KRAS-mutant non-small cell lung cancer by inhibiting the PDGF-BB-induced SRC/MAPK/AP-1/PD-L1 signaling pathway and potentiating the antitumor effect of an anti-PD-1 antibody - Li, Jia-Xin; Tan, Shi-Yu; Li, Li-Qi; Zheng, Yu-Hong; Zhao, Lin; Zhu, Hui-Rong; He, Hai-Lang; Zhang, Yan-Yu; Li, Run-Ze; Bao, Tian-Yu; Zhang, Yi-Zhong; Yang, Xiao-Man; et al. (Frontiers in Pharmacology, 2025)
BackgroundKRAS is a commonly mutated gene that is present in approximately 30% of NSCLC patients. Currently, the identification of effective therapies for KRAS-mutant NSCLC is difficult for reasons of the structural and biochemical characteristics of the KRAS protein. Our previous study has revealed that tricin was a bioactive component having selective effects on KRASG12C-mutant NSCLC cell lines. Thus, our aim in this project was to explore the mechanism by which tricin inhibited the progression of KRAS-mutant NSCLC much more deeply.MethodsFirst of all, we detected the acute toxicity of an intraperitoneal injection of tricin in mice according to the improved up-and-down procedure. Next, we integrated network pharmacology, molecular docking with transcriptomics analysis and biological methods to probe the underlying mechanisms of tricin in the treatment of patients with KRAS-mutant NSCLC. Furthermore, we explored the pharmaceutical effects of combination therapy with tricin and an anti-PD-1 inhibitor. Finally, we detected and analyzed the data from clinical samples to prepare for the clinical translation of tricin.ResultsIntraperitoneal injection of tricin resulted in low acute toxicity. In vitro, tricin inhibited the migration, proliferation and colony formation of KRASG12C-mutant NSCLC cells in a dose-dependent manner. Mechanistically, tricin inhibited KRASG12C-mutant NSCLC cell growth primarily by suppressing the PDGF-BB-induced SRC/MAPK/AP-1/PD-L1 signaling pathway. SRC was identified as a potentially crucial target. In vivo, combined treatment with tricin and an anti-PD-1 antibody markedly suppressed the growth of tumors. The combination treatment had nearly no toxicity to the organs of the mice. In terms of immune regulation, tricin increased the numbers of CD8+ T lymphocytes and the levels of the functional cytokines TNFα, IFNγ, and Granzyme B. Tricin also increased the numbers of B lymphocytes and disrupted the PD-1/PD-L1 pathway. These results indicated that tricin could compensate for the deficiency of immunotherapy and enhance the antitumor activity of immunotherapy. Moreover, the detection of clinical samples indicated that the rate of SRC positivity was higher in elderly patients with KRAS mutations at the early stage. A positive correlation between the expression of SRC and PD-L1 was observed in tumor tissues.ConclusionWe believe that tricin is a safe and promising agent for the treatment of patients with KRAS-mutated NSCLC. Our study provides an experimental basis for improving the clinical application of traditional Chinese medicine.